Histological and hormonal changes in the European eel (Anguilla anguilla) after exposure to environmental cocaine concentration. Issue 3 (10th April 2015) - Gay, F; Ferrandino, I; Monaco, A; Cerulo, M; Capasso, G; Capaldo, A
Abstract: The aim of this study was the assessment of histological and hormonal changes induced in the European eel from environmental concentrations of cocaine. Silver eels were exposed to 20 ng L −1 of cocaine during 50 days; at the same time, control, vehicle control and two post‐exposure recovery groups (3 and 10 days) were made. The general morphology of the skin and the intestine, and the plasma levels of prolactin, cortisol and dopamine were evaluated. In the skin, cocaine decreased the number and size of mucous cells, increased the thickness of the epidermis and altered the club cells and the basal lamina. In the intestine, cocaine increased the thickness of the epithelium and the number of mucous cells and reactivated the structure of the intestine and of the intestinal musculature. Moreover, cocaine increased plasma prolactin, cortisol and dopamine levels. These results suggest that cocaine induced histological changes, directly and/or through the hormonal changes observed. Considering the complex life cycle of the eel, the changes induced by cocaine in the skin, the intestine and the endocrine system could threaten the ability of the eel to successfully migrate and reproduce.